Conflicts in Industrial Organizations and Transition: The Case of Serbia - Šljukić, Marica N.; Šljukić, Srđan Lj. (Sociološki pregled, 2019)
The combination of external and internal transition factors has not only influenced the devastation of Serbian industry over time, but it has caused a number of organizational changes in the remaining and newly formed industrial organizations. The paper focuses on the factors that have led to a change in position and a reduction in the power of industrial workers and that affect their attitudes to conflicts in the organization. Drawing on empirical data from 2001 and 2011-2013, and assuming that it is possible to expect the tolerance of conflicts as such and their regulation in the industrial sphere (which is the practice in developed capitalist societies), the authors are trying to find out whether and to what extent conflicts in industrial organizations in Serbia have been institutionalized.
Keywords: transition; Serbia; industrial organizations; conflict; institutionalization